PENGARUH PERSEPSI RISIKO DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE SAAT TERJADI PANDEMI COVID-19 DI BUNGUS TELUK KABUNG - Riche Fermayani; Ash Shadiq Egim; Al Hayyu Al Hayyu (Bisnis-Net, 2023)
Abstract Â This study aims to determine the effect of risk perception and trust on online purchasing decisions during the Covid-19 pandemic in BungusTelukKabung. The total population of this study was 125,415 while the number of samples studied in this study were 100 respondents based on the slovin formula. From the partial t test, it can be explained that the significance value of risk perception is 0.266 > 0.05, it can be concluded that the risk perception variable has a negative and insignificant effect on online purchasing decisions, and the trust significance value is 0.000 < 0.05, so it can be concluded that the trust variables has a positive and significant effect on online purchasing decisions. Based on the simultaneous f-test, a significance value of 0.000 <alpha 0.05 was obtained, it can be concluded that the risk perception and trust variables together influence online purchasing decisions. The magnitude of the influence of the independent variable on the dependent variable is 19.10% while the remaining 80.90% is influenced by other variables that are not included in the research model.Keywords: Risk Perception, Trust and Online Purchase Decision.